INNV-37. XCELSIOR: A REAL-TIME, REAL-WORLD LEARNING PLATFORM FOR PATIENTS WITH ADVANCED CANCER. (12th November 2021) - Stuhlmiller, Timothy; Shapiro, Mark; Wasserman, Asher; Osking, Zachary; Shrager, Jeff; Federowicz, Bryan; Warner, Matthew; Friedland, Julie; Musella, Al; Blondin, Nicholas; Fonkem, Ekokobe; Wong, Eric; et al.
Abstract: xCures operates a direct-to-patient, real-world evidence platform for decentralized clinical research. The platform leverages a nationwide observational research protocol (XCELSIOR, NCT03793088 ) to aggregate, normalize, and analyze N-of-1 clinical outcomes to continuously learn from and inform treatment decisions. Individual data elements are extracted directly from medical documents such as clinic notes, and radiology, genomics, and pathology reports. The data elements are standardized to established biomedical ontologies and stored in a validated and part 11 compliant electronic database, suitable for statistical analyses and regulatory filings. This permits comparison of patient outcomes across institutions and removes the burden of data entry from oncologists and their staff. As an extremely efficient real-world data solution, we have utilized this platform to accelerate both academic- and commercial-sponsored clinical research, prospectively integrating diagnostics and algorithms with interventional treatments. For each patient that participates in XCELSIOR, artificial intelligence-powered clinical decision support algorithms suggest testing and treatment options. These options and supporting treatment rationales are sourced from key opinion leaders, tumor boards, clinical researchers, practicing oncologists, and published literature, and ranked using the real-world outcomes data from the registry. At the conference, we will present an overview of this real-time learning infrastructure and report on clinical case studies for pharma and non-profit groups including over 75 virtual tumor boards and real-world evidence generated from over 150 patients with CNS cancers that we have helped in partnership with Cancer Commons and The Musella Foundation for Brain Tumor Research and Education. Outcomes analyses stratified by therapeutic interventions and biomarkers will be reported, including frequency of adverse events, time to treatment failure, time to disease progression, and overall survival. Interventions include standard-of-care chemotherapies as well as therapies accessed by clinical trial, expanded access, and off-label prescription.